Feasibility Study for Developing Santari Island as a Natural Tourism Object in North Obi District, South Halmahera Regency - Jainudin Hasim; Asnita Ode Samili; Syarifuddin Adjam (CV Edujavare Publishing, 2026)
This study aims to analyze the feasibility of developing Santari Island as a natural tourism destination in North Obi District, South Halmahera Regency. The method used is descriptive with a mixed methods approach through observation, interviews, questionnaires, and documentation. Data analysis was conducted descriptively and used a SWOT analysis to formulate a development strategy. The results of the study indicate that Santari Island has great potential in terms of natural, socio-cultural, and economic aspects, with advantages such as beautiful beaches, pristine marine ecosystems, and support from the local community. However, there are several obstacles such as limited accessibility, minimal infrastructure, low human resource capacity, and weak promotion. Multidimensionally, Santari Island is considered feasible for development with the note that improvements in technical and managerial aspects are needed. Recommended development strategies include infrastructure development, community capacity building, promotion optimization, and the implementation of environmentally-based management. With an integrated and sustainable approach, Santari Island has the potential to become a leading tourist destination that can improve community welfare while preserving the environment.